Geoidal correction methods for GPS geodetics measurements (Geoidal correction) - Franco, Luis; Hoyer, Melvin (Rev. Téc. Fac. Ing. Univ. Zulia, 2011)
This work analyzes the problem of fixing GPS ellipsoidal heights by geoidal undulation effects. It studies some correction models that some institutes use for that purpose, here in Venezuela; testing them on a previously selected test network. Analyzing the results obtained on the different tests, comparing them with the height values of the points in the DCN system, with special emphasis on the differences between them. Conclusions and recommendations are presented to GPS users with respect to the advantages and disadvantages of each geoidal correction model.